Solar Ultraviolet Radiation Measurements in One of the Most Populous Cities of the World: Aspects Related to Skin Cancer Cases and Vitamin D Availability - De Paula Corrêa, Marcelo; Ceballos, Juan Carlos (Photochemistry and photobiology, 2010)
A number of studies published in the scientific literature have shown the relationship between sun exposure and nonmelanoma skin cancer (NMSC) and vitamin D synthesis. However, the paucity of medical data, particularly in developing countries, hampers a global assessment of the impact of sun exposure on NMSC and vitamin D. To improve knowledge on this subject, this paper presents UV index (UVI) measurements performed in São Paulo City (SPC) in the period 2005–2008. It was found that 65% of the UVI measured 2 h around local noon during the summer show very high (8 < UVI < 10) and extreme (UVI > 11) levels according to the World Health Organization (WHO) classification. During the winter, 40% of the measurements around noontime show high or very high levels. In spite of worrisome recent statistics from SPC, showing that NMSCs make up about 28% of over a million of new cases of cancer in 2008, sun protection is not considered a real problem in these urban areas. UV measurements also show that every month of the year UV levels are high enough to ensure vitamin D production in human skin from incidental sun exposure.